Pengaruh Digital Marketing terhadap Loyalitas Konsumen dengan Preferensi Konsumen sebagai Mediator: Studi Kasus pada produk Kerupuk Finna Food - Sugeng, Janice Violensia; Aurellita, Gavina; Wijaya, Verina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
In the food and beverage industry, social media platforms play an important role in creating interactive communication and building customer loyalty. This study aims to examine the influence of digital marketing on customer loyalty with consumer preference as a mediating variable among consumers of shrimp crackers produced by Finna Food. The research applies a quantitative approach using purposive sampling. A total of 100 respondents who have purchased Finna Food products and follow the company’s official Instagram account were selected as the sample. Primary data were collected through an online questionnaire using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that digital marketing has a positive and significant effect on both customer loyalty and consumer preference. Furthermore, consumer preference also significantly influences customer loyalty. Mediation testing confirms that consumer preference significantly mediates the relationship between digital marketing and customer loyalty. These results indicate that effective digital marketing strategies are able to shape positive consumer preferences, which ultimately strengthen customer loyalty toward the brand. Therefore, companies are advised to develop more interactive, engaging, and relevant digital marketing content in order to enhance customer engagement, strengthen consumer preferences, and sustain long-term customer loyalty in an increasingly competitive digital marketplace environment. Keywords: digital marketing, customer preference, customer loyalty